2013
DOI: 10.1007/s12105-013-0431-6
|View full text |Cite
|
Sign up to set email alerts
|

Moderately Differentiated Neuroendocrine Carcinoma (Atypical Carcinoid) of the Parotid Gland: Report of Three Cases with Contemporary Review of Salivary Neuroendocrine Carcinomas

Abstract: Primary neuroendocrine carcinomas (NECs) of the salivary glands are rare. Most reported NECs in that region are small cell carcinomas with few cases of large cell undifferentiated carcinoma and typical carcinoid tumors. Only two moderately differentiated NECs (atypical carcinoid tumors) have been previously reported. In the current series, the authors report three additional moderately differentiated NECs (atypical carcinoid tumors) of the parotid gland; two occurred in women and one in a man. All patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 54 publications
0
24
0
2
Order By: Relevance
“…Wenig et al [3] in their series of ''moderately differentiated'' NEC reported that 38 % (18/48) of patients had died with tumor. One of two patients with ''moderately differentiated NEC'' of parotid gland described by Said-Al-Naief [28] was alive with liver metastases whereas the patient illustrated by Modlin et al [29] was alive with stable metastatic disease in the liver 10 years after initial diagnosis. We stress the need of collaborative studies with current diagnostic criteria to determine the differences in behavior, prognosis, and molecular genetic underpinnings between the old ''atypical carcinoid tumors'' and ''LC-NECs'' in the head and neck.…”
Section: The 2005 World Health Organization (Who)mentioning
confidence: 99%
See 1 more Smart Citation
“…Wenig et al [3] in their series of ''moderately differentiated'' NEC reported that 38 % (18/48) of patients had died with tumor. One of two patients with ''moderately differentiated NEC'' of parotid gland described by Said-Al-Naief [28] was alive with liver metastases whereas the patient illustrated by Modlin et al [29] was alive with stable metastatic disease in the liver 10 years after initial diagnosis. We stress the need of collaborative studies with current diagnostic criteria to determine the differences in behavior, prognosis, and molecular genetic underpinnings between the old ''atypical carcinoid tumors'' and ''LC-NECs'' in the head and neck.…”
Section: The 2005 World Health Organization (Who)mentioning
confidence: 99%
“…Lower grade neuroendocrine carcinomas (''typical carcinoid'' and ''atypical carcinoid'' tumors) of salivary gland origin are extremely rare [4,28,29,41]. The recognition of LC-NEC in salivary glands was hampered by the absence of well defined microscopic criteria for their diagnosis and the lack of ancillary techniques to demonstrate neuroendocrine differentiation; however, NEC, large cell-type (LC-NEC) in the major salivary glands was recognized in 1990 by Hui et al [21] in what is probably the most cited study of ''undifferentiated'' carcinomas of the salivary glands.…”
Section: The 2005 World Health Organization (Who)mentioning
confidence: 99%
“…SmCC has also been referred to as oat cell carcinoma, poorly differentiated neuroendocrine carcinoma, small cell undifferentiated carcinoma, or anaplastic cell carcinoma (2,5). SmCC may also occur in non-pulmonary organs in which it is classified as extra-pulmonary small cell carcinoma (EPSmCCs).…”
Section: Discussionmentioning
confidence: 99%
“…The cells are typically identified by ill-defined borders, sparse eosinophilic cytoplasm, and pyknotic nuclei, with fine evenly-dispersed clumped chromatin. Nuclear molding and crush artifact may also be observed in these cases, and the nucleoli are inconspicuous (3,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation